UPAYA MENINGKATKAN KREATIVITAS DAN KEMAMPUAN MENGAPRESIASI DRAMA MELALUI PEMENTASAN DRAMA - Cicih Wiarsih (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This study attempts to improve the creativity and the ability to appreciate drama on the ability of Indonesian courses through drama performances. This research was conducted in FKIP PGSD Studies Program, University of Muhammadiyah Purwokerto second semester of academic year 2015/2016. Subjects were students of the second semester of grade E as many as 44 students. The procedure of research is classroom action research conducted in two cycles. Each cycle consists of planning, action, observation, and reflection. The research instrument used creativity test playwriting and performance tests, while observing the activity of faculty and students using observation sheet. The results showed that the staging of the drama can increase creativity playwriting and drama to appreciate the ability of the student. This is evidenced by the increasing creativity of students of the first cycle with an average score of 9.74 to the criteria are quite creative and the second cycle with an average score of 12.07 with creative criteria. This suggests that an increase in the creativity of students from the first cycle to the second cycle of 2.33. In the aspect of ability to appreciate the drama of an increase of 43.76 from the first cycle to gain an average score of 44.34 to the second cycle with an average score of 88.10. Based on the above results, it can be concluded that by staging the drama can enhance the creativity and the ability to appreciate the drama students of the second semester in the subject's ability Indonesian elementary school. Keywords: creativity, the ability to appreciate the drama, and drama performances